Analytical modeling of a DCFL inverter using normally-off GaAs MESFET's under dark and illuminated conditions - Jit S.; Bandhawakar G.; Pal B.B. (My University, 2025)
An analytical model has been presented to study the characteristics of a DCFL (Direct Coupled FET Logic) inverter using normally-off GaAs MESFET's (E-MESFET's) under dark and illuminated conditions. Optical illumination is provided at the gate area of the MESFET with a transparent/semi-transparent metal at the Schottky junction of the device. The photovoltage developed across the Schottky junction due to the illumination may be used to control the characteristics of the inverter circuit. The transfer characteristics of the inverter with fanout = 0 and 1 have been presented under both the dark and illuminated conditions. It has been observed that the circuit may change its state from high to low logic level by simply changing the illumination level provided on the gate-area of the switching E-MESFET. © 2005 Elsevier Ltd. All rights reserved.